2021
DOI: 10.1111/odi.13828
|View full text |Cite|
|
Sign up to set email alerts
|

LINC00460 facilitated tongue squamous cell carcinoma progression via the miR‐320b/IGF2BP3 axis

Abstract: Objective We aimed to explore the role of long intergenic non‐protein coding RNA 460 (LINC00460) in tongue squamous cell carcinoma (TSCC). Methods We enrolled 27 TSCC patients to explore LINC00460 expression in clinical TSCC samples. RT‐qPCR measured expression of molecules in this research. Loss‐of‐function assays explored biological function of LINC00460 in TSCC cells. RNA pull‐down assay, luciferase reporter assay, and RIP assay investigated mechanism of LINC00460 underlying TSCC cells. Results TSCC tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…However, IGF2BP3 is well-known as a member of insulin-like growth factor-2 mRNA-binding proteins, and promote target mRNAs stability and translation as a N6-methyladenosine (m 6 A) reader, such as IGF2, MYC, ACTB and AML, which is also present in multiple tissues and mainly associated with tumorigenesis and tumor development as a biomarker of cancer [51][52][53][54][55][56]. In recent two years, there were a few miRNAs have been reported to target IGF2BP3 for the regulation of different tissue and cancer cells proliferation and invasion, such as mi-127-5p, miR-9-5p, miR-370, miR-142-5p, miR-320b and so on [57][58][59][60][61]. Although there was no direct report of IGF2BP3 participated in ovarian steroid synthesis, some studies have reported IGF2BP3 modulated early embryo and oocyte development in aqua [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…However, IGF2BP3 is well-known as a member of insulin-like growth factor-2 mRNA-binding proteins, and promote target mRNAs stability and translation as a N6-methyladenosine (m 6 A) reader, such as IGF2, MYC, ACTB and AML, which is also present in multiple tissues and mainly associated with tumorigenesis and tumor development as a biomarker of cancer [51][52][53][54][55][56]. In recent two years, there were a few miRNAs have been reported to target IGF2BP3 for the regulation of different tissue and cancer cells proliferation and invasion, such as mi-127-5p, miR-9-5p, miR-370, miR-142-5p, miR-320b and so on [57][58][59][60][61]. Although there was no direct report of IGF2BP3 participated in ovarian steroid synthesis, some studies have reported IGF2BP3 modulated early embryo and oocyte development in aqua [62,63].…”
Section: Discussionmentioning
confidence: 99%
“… 65 Therefore, it can be speculated that competitive binding to miRNAs can also up-regulate IGF2BPs in cancers, and recent studies have confirmed this hypothesis. 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 Interestingly, IGF2BP3 stabilizes the lncRNA KCNMB2-AS1 in an m 6 A methylation-dependent manner, while KCNMB2-AS1 sponges miR-130b-5p and miR-4294 can induce the up-regulation of IGF2BP3, 77 which then forms a positive feedback loop in cervical cancer. The mRNA of IGF2BP1 or IGF2BP3 is stabilized by the lncRNA THOR or DARS-AS1 in cancer cells.…”
Section: The Regulation Of Igf2bps In Cancersmentioning
confidence: 99%
“…The expression of lncRNA-PNUTS is elevated and correlates with the mRNA level of ZEB1. A number of lncRNAs have been identified as EMT modulators in oral cancer [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 ,…”
Section: Epithelial-to-mesenchymal Transition: Emtmentioning
confidence: 99%